Effect of a Weight Loss Program on Biochemical and Immunological Profile, Serum Leptin Levels, and Cardiovascular Parameters in Obese Dogs - Piantedosi, Diego; Palatucci, Anna Teresa; Giovazzino, Angela; Ruggiero, Giuseppina; Rubino, Valentina; Musco, Nadia; Carriero, Flavia; Farina, Fortunata; Attia, Youssef Abd El Wahab; Terrazzano, Giuseppe; Lombardi, Pietro; Cortese, Laura (Frontiers in Veterinary Science, 2020)
This study aimed to investigate the effects of a weight loss program (WLP) on biochemical and immunological profile, and cardiovascular parameters in a cohort of dogs with naturally occurring obesity. Eleven obese dogs (BCS ≥ 7/9) were enrolled into the study and underwent clinical and cardiovascular examination, and blood testing before (T0) and after 6 months (T1) of WLP. Eleven normal weight (BCS 4/5) healthy dogs were used as a control group (CTR). Compared to CTR group, at T0 obese dogs expressed higher serum leptin concentrations (p < 0.0005) that significantly decreased after weight loss (p < 0.005), but remained higher than CTR group. Furthermore, obese dogs showed considerably lower levels (p < 0.0005) of regulatory T cell (Treg) compared to CTR group, but they did not change after weight loss at T1. In obese dogs, Tumour necrosis factor (TNF)-α and interleukin (IL)-6 concentrations were substantially reduced at T1 (p < 0.0001 and p <0.005). Regarding the cardiovascular parameters, only one obese dog was hypertensive at T0 and systolic blood pressure values showed no significant differences at the end of the WLP. The ratio of interventricular septal thickness in diastole to left ventricle internal diameter in diastole (IVSd/LVIDd) was significantly greater in obese dogs at T0 than CRT group (p < 0.005). It decreased after weight loss (p <0.05). In obese dogs, troponin I level significantly reduced with weight loss (p < 0.05), while Endothelin-1 level did not differ statistically. The results suggest that the immune dysregulation in presence of high leptin levels and reduced number of Treg, could affect obese dogs as well as humans. Based on our findings, we may speculate that a more complete immune-regulation restore could be obtained by a greater reduction in fat mass and a longer-term WLP. Finally, left ventricular remodelling may occur in some obese dogs. However, in canine species further studies are needed to investigate the impact of obesity and related WLP on cardiovascular system.